Design and Analysis of Circular Patch Antenna. Issue 1 (February 2021) - Kumar, Bayana Lalith Venkat; Pramod, Chennupalli Bhaskar; Nagendram, S; Kalyan, SSS
Abstract: The ANSI-based circular microstrip patch antenna is designed to work at 7.4GHz and 12GHz using HFSS simulator software for various WLN (Wireless Local Area Network) applications, Bluetooth, and IoT communications. The circular patch antenna is made using FR4, which is 4.4 KE, 1.6 mm high, and has a gain of 3 dB. It tests countless antenna features such as return loss, radiation adjustment, bandwidth, directivity, antenna gain, and radiation productivity.